2022
DOI: 10.1177/08968608221077461
|View full text |Cite
|
Sign up to set email alerts
|

Technique failure in peritoneal dialysis: Modifiable causes and patient-specific risk factors

Abstract: Background: Technique survival is a core outcome for peritoneal dialysis (PD), according to Standardized Outcomes in Nephrology-Peritoneal Dialysis. This study aimed to identify modifiable causes and risk factors of technique failure in a large Dutch cohort using standardised definitions. Methods: Patients who participated in the retrospective Dutch nOcturnal and hoME dialysis Study To Improve Clinical Outcomes cohort study and started PD between 2012 and 2016 were included and followed until 1 January 2017. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
0
17
2
Order By: Relevance
“…It is worth mentioning, however, that all patients who stopped PD for psychosocial reasons in our study were men. Psychosocial reasons were the top cause of PD discontinuation in our data, which is different from what has been found in Australia/New Zealand, Netherlands, and France, where psychosocial factors played a smaller role compared to infectious and mechanical complications [27][28][29]. In our experience, patients' realization of the commitment needed to perform PD and lack of adequate family support were the main drivers of PD discontinuation, which could be traced to suboptimal patient and family education before initiating PD The two factors associated with an increased risk of death were lacking residual urine output at the time of PD initiation and not having PD as the rst treatment modality.…”
Section: Discussioncontrasting
confidence: 99%
“…It is worth mentioning, however, that all patients who stopped PD for psychosocial reasons in our study were men. Psychosocial reasons were the top cause of PD discontinuation in our data, which is different from what has been found in Australia/New Zealand, Netherlands, and France, where psychosocial factors played a smaller role compared to infectious and mechanical complications [27][28][29]. In our experience, patients' realization of the commitment needed to perform PD and lack of adequate family support were the main drivers of PD discontinuation, which could be traced to suboptimal patient and family education before initiating PD The two factors associated with an increased risk of death were lacking residual urine output at the time of PD initiation and not having PD as the rst treatment modality.…”
Section: Discussioncontrasting
confidence: 99%
“…It is worth mentioning, however, that all patients who stopped PD for psychosocial reasons in our study were men. Psychosocial reasons were the top cause of PD discontinuation in our data, which is different from what has been found in Australia/New Zealand, Netherlands, and France, where psychosocial factors played a smaller role compared to infectious and mechanical complications [27][28][29]. In our experience, patients' realization of the commitment needed to perform PD and lack of adequate family support were the main drivers of PD discontinuation, which could be traced to suboptimal patient and family education before initiating PD.…”
Section: Discussioncontrasting
confidence: 96%
“…Recent studies have found that the APD modality is associated with a reduced risk of technique failure compared to CAPD [ 13 , 15 , 16 ]. Therefore, elevated BMI and reduced serum albumin levels are also regarded as being predictors of peritoneal dialysis withdrawal and all-cause mortality [ 17 , 18 ], and diabetes, cardiovascular disease, and other complications appear to be risk factors for death or switching to HD [ 13 , 19 ]. Employment status and educational level may be different in people with and without technique failure [ 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medical cure was defined as the complete resolution (culture of PD effluent was confirmed negative following appropriate treatment, with a PD effluent white cell count lower than 100/μL) together with a lack of the following complications: relapse/recurrent peritonitis, catheter removal, transfer to HD for ≥30 days, or death during the 30 days after onset of peritonitis episode [ 1 , 2 , 13 ]. Moreover, PD technique failure was defined as the transfer to in-center HD for greater than 30 days or PDRP-associated death, which was defined as death within 30 days of the onset of PDRP [ 1 , 2 , 13 ].…”
Section: Methodsmentioning
confidence: 99%